2018
DOI: 10.1111/1477-9552.12309
|View full text |Cite
|
Sign up to set email alerts
|

The Local Impacts of Agricultural Subsidies: Evidence from the Canadian Prairies

Abstract: We estimate the impact of removing an export subsidy on the local economies of Alberta, Saskatchewan and Manitoba, exploiting the large regional variation of a 1995 reform. We find that the loss of the subsidy resulted in significantly lower farm value-added, farm asset values and local non-farm employment. The results suggest that the subsidy removal had detrimental spillover effects on the local nonagricultural economy that varied spatially across the Prairies. The point estimates suggest that the marginal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Since the implementation of the agricultural subsidy policy, scholars have conducted fruitful research on the effect of agricultural subsidy policies but have not reached consensus [ 7 , 8 , 9 ]. From the perspective of agricultural subsidies’ effects on farmers’ initiative for growing grain, some scholars found that they have a marginal incentive effect and play a positive role for farmers who are uncertain about participating in grain planting, improving farmers’ enthusiasm for grain planting and increasing the sown area [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the implementation of the agricultural subsidy policy, scholars have conducted fruitful research on the effect of agricultural subsidy policies but have not reached consensus [ 7 , 8 , 9 ]. From the perspective of agricultural subsidies’ effects on farmers’ initiative for growing grain, some scholars found that they have a marginal incentive effect and play a positive role for farmers who are uncertain about participating in grain planting, improving farmers’ enthusiasm for grain planting and increasing the sown area [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Second, for the impact on sustainable agricultural society, Bollman and Ferguson [ 13 ] find that fiscal subsidy cancellation has negative spillover effects on the local non-agricultural economy, leading to significant reductions in farm value-added, farm asset value, and local non-farm employment. With statistical models, Diallo and Wouterse [ 14 ] and Sánchez et al [ 15 ] simulate the potential impacts of fiscal agricultural investment and conclude that public investment led by agricultural productive infrastructure will significantly promote agricultural growth, thereby reducing dependence on food imports, raising income from food production and reducing poverty, which is conducive to economic recovery after the COVID-19 pandemic.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…a regression model with a product term is used to test and construct the following equation to test the moderating effect model of operation scale: In Equations ( 5) to (7), represents the moderation variable, represents the product term of the independent variable and the moderation variable, and represents the product term of the mediation variable and the moderation variable.…”
Section: Mediated Moderation Modelmentioning
confidence: 99%